Uma revisão bibliográfica sobre o ensino de Física por meio das Histórias em Quadrinhos - CABRAL, Valéria da Costa (2022)
Knowing the importance that the teacher has to awaken in the student the motivation and interest in learning, this work presents a bibliographical review with the objective of emphasizing on the importance of the use of Comics (HQs) and Cordel Literature (LC) as educational resources for the teaching-learning process of physics in schools. And to fulfill this objective, the method of bibliographical research was used in academic articles, books and websites that bring a study on the mentioned topic and that shows the importance of these didactic resources in classes during teaching practice. The revised works present us with a contextualized and dynamic way of teaching and learning, which takes into account the students' knowledge and reality, which for the authors facilitates not only the teachinglearning process, but also the teacher-student relationship. This work made it possible to understand that the contextualization of physics content addressed through comics and LC brings science closer to art and allows students to study and learn through creativity and interdisciplinarity, increasing their imaginative capacity and stimulating their development, as the worked readings bring an easy-to-understand writing, where the content is presented in a simple, fun and humorous way, which attracts the student's attention, making him feel interested in learning physics, and stating that by bringing science and literature together in education we can build scientific knowledge.